2021
DOI: 10.3389/fnut.2021.688715
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-2 Modulates Enteric Paneth Cells Immune Response and Alleviates Gut Inflammation During Intravenous Fluid Infusion in Mice With a Central Catheter

Abstract: Background: Glucagon-like peptide-2 (GLP-2) has protective effects on gastrointestinal functions. Our previous study found that GLP-2 could significantly reduce intestinal permeability and bacterial translocation in total parenteral nutrition (TPN) animal model. However, the effects of GLP-2 on the impairment of the intestinal Paneth cells immune function and gut inflammation during intravenous fluid infusion mainly consisted of nutritional materials is currently scattered.Objective: The current study was aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The immunofluorescence experiment was followed the previous pattern with minor modifications ( 25 ). The sections (20 μm thick) were mounted on glass slides and washed for 15 min in PBS containing 0.2% Tween-20 (PBST).…”
Section: Methodsmentioning
confidence: 99%
“…The immunofluorescence experiment was followed the previous pattern with minor modifications ( 25 ). The sections (20 μm thick) were mounted on glass slides and washed for 15 min in PBS containing 0.2% Tween-20 (PBST).…”
Section: Methodsmentioning
confidence: 99%
“…To date, there is a lack of research on the direct role of IGF signaling in the normal function of PLCs or the interaction between the IGF system and autophagy in these colonic cells. In contrast, IGF-1 has been shown to be an important mediator of the tropic effect of glucagon-like peptide 2 (GLP-2), which attenuated small intestinal inflammation and improved the immune response of intestinal PCs in the total parenteral nutrition animal model of a study [ 185 ].…”
Section: Autophagy In Normal Large Intestine Epithelial Cells—implica...mentioning
confidence: 99%
“…In addition to its protective and growth promoting roles in the intestine, GLP-2 exerts anti-inflammatory effects through multiple different mechanisms. For instance, GLP-2 dampened pro-inflammatory cytokine production in LPS-treated macrophages through inhibiting NF-κB activity and ERK phosphorylation [ 131 ] and reducing mucosal inflammatory responses [ 132 ] in mice, while in a model of obstructive jaundice in rats, GLP-2 reduced serum levels of TGF-β1, bilirubin, and endotoxin, which improved intestinal barrier function [ 133 ]. Interestingly, data from animal models of intestinal barrier dysfunction in mice, rats, and piglets underlines the importance and protective action of GLP-2 in inflammation-mediated intestine injuries [ 58 , 134 , 135 ].…”
Section: Glp-1 and Glp-2 As Regulators Of Intestine Integrity And Inf...mentioning
confidence: 99%
“…While parenteral nutrition remains the life-saving standard for nutrient delivery in patients with intestinal failure, serious complications may develop such as liver and intestinal mucosal barrier injury, inflammation, and bacterial translocation [ 137 , 138 ]. To further understand the role of GLP-2 to ameliorate parenteral nutrition-associated gut injury, using a mouse model of parenteral nutrition, Deng et al, showed that GLP-2 significantly suppressed the expression of pro-inflammatory cytokines TNF-a and IL-6 in the ileum and reduced serum levels of D-lactic acids and LPS [ 132 ].…”
Section: Glp-1 and Glp-2 As Regulators Of Intestine Integrity And Inf...mentioning
confidence: 99%